Pengaruh Status Ekonomi Orang Tua dan Potensi Diri terhadap Minat Siswa SMA Melanjutkan Ke Perguruan Tinggi - Resta Sari Wahyuni; Edi Harapan; Nurlina Nurlina (Journal on Education, 2023)
This research is based on the problem of the low interest of public high school students in Ogan Komering Ilir (OKI) Regency to continue their studies at tertiary institutions. Evidenced by the percentage of students who go on to tertiary education from SMAN in OKI Regency on average below 50%. The purpose of this study was to determine and analyze the influence of parents' economic status and self-potential on high school student's interest in continuing to tertiary education in public high schools in Ogan Komering Ilir Regency. This research was conducted at public high schools in Ogan Komering Ilir Regency in the odd semester of the 2022/2023 academic year. The time needed for this research starts from June to November 2022. This research will look for the influence between variables, namely the economic status of parents and self-potential on the interest of high school students to continue to college. The results of the analysis succeeded in proving the hypothesis proposed in this study, where the variables of Parents' Economic Status and Self-Potential simultaneously had a significant effect on the Interests of SMAN Students to continue to Higher Education. The influence contributed by these two variables is R2 = 0.390 (39%), the value indicates a "high" relationship category because it is in the range of 0.300 – above. the contribution of parents' economic status variables and self-potential variables partially and simultaneously affect the interest variables of SMAN students in Ogan Komering Ilir Regency significantly. While contributions from other variables that are not accurate are 61%.